Question
upstudy study bank question image url

5A) Solve the system of equations using a method of your choice. \[ \begin{array}{l}8 x-3 y=-1 \\ x+2 y=-12\end{array} \] 5B) Solve the system of equations using a different method.

Ask by Willis Willis. in the United States
Jan 13,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution to the system of equations is \( x = -2 \) and \( y = -5 \).

Solution

Certainly! Let's solve the given system of equations using two different methods for parts **5A** and **5B**. \[ \begin{cases} 8x - 3y = -1 \quad \text{(Equation 1)} \\ x + 2y = -12 \quad \text{(Equation 2)} \end{cases} \] --- ### **5A) Solving by Substitution Method** **Step 1: Solve one equation for one variable** Let's solve **Equation 2** for \( x \): \[ x + 2y = -12 \\ \Rightarrow x = -12 - 2y \] **Step 2: Substitute this expression into the other equation** Substitute \( x = -12 - 2y \) into **Equation 1**: \[ 8(-12 - 2y) - 3y = -1 \\ -96 - 16y - 3y = -1 \\ -96 - 19y = -1 \] **Step 3: Solve for \( y \)** \[ -19y = -1 + 96 \\ -19y = 95 \\ y = \frac{95}{-19} \\ y = -5 \] **Step 4: Substitute \( y \) back to find \( x \)** Using \( x = -12 - 2y \): \[ x = -12 - 2(-5) \\ x = -12 + 10 \\ x = -2 \] **Solution:** \[ x = -2, \quad y = -5 \] --- ### **5B) Solving by Elimination Method** **Step 1: Align the equations** \[ \begin{cases} 8x - 3y = -1 \quad \text{(Equation 1)} \\ x + 2y = -12 \quad \text{(Equation 2)} \end{cases} \] **Step 2: Make the coefficients of one variable the same** Let's eliminate \( x \). Multiply **Equation 2** by 8: \[ 8(x + 2y) = 8(-12) \\ 8x + 16y = -96 \quad \text{(Equation 3)} \] **Step 3: Subtract **Equation 1** from **Equation 3** to eliminate \( x \)** \[ (8x + 16y) - (8x - 3y) = -96 - (-1) \\ 8x + 16y - 8x + 3y = -95 \\ 19y = -95 \] **Step 4: Solve for \( y \)** \[ y = \frac{-95}{19} \\ y = -5 \] **Step 5: Substitute \( y \) back to find \( x \)** Using **Equation 2**: \[ x + 2(-5) = -12 \\ x - 10 = -12 \\ x = -12 + 10 \\ x = -2 \] **Solution:** \[ x = -2, \quad y = -5 \] --- Both methods lead to the same solution: \[ \boxed{(x, y) = (-2,\ -5)} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations \(8x - 3y = -1\) and \(x + 2y = -12\) using the substitution method, first, solve the second equation for \(x\): \[ x = -12 - 2y. \] Now substitute this expression for \(x\) into the first equation: \[ 8(-12 - 2y) - 3y = -1. \] This simplifies to: \[ -96 - 16y - 3y = -1 \] \[ -19y = 95 \] \[ y = -5. \] Substituting \(y\) back into the expression for \(x\): \[ x = -12 - 2(-5) = -12 + 10 = -2. \] So, the solution is \((x, y) = (-2, -5)\). Now, let’s solve it using the elimination method. Start with the original equations: 1) \(8x - 3y = -1\) 2) \(x + 2y = -12\) To eliminate \(x\), we can multiply the second equation by 8: \[ 8x + 16y = -96. \] Now, subtract the first equation from this new equation: \[ (8x + 16y) - (8x - 3y) = -96 - (-1), \] which simplifies to: \[ 19y = -95. \] This gives us \(y = -5\). Now substitute \(y\) back into the second original equation: \[ x + 2(-5) = -12 \] \[ x - 10 = -12 \] \[ x = -2. \] So again, the solution is \((x, y) = (-2, -5)\).

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy